2007
DOI: 10.1016/j.brainres.2006.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Loss of calcium and increased apoptosis within the same neuron

Abstract: Loss of neuronal calcium is associated with later apoptotic injury but observing reduced calcium and increased apoptosis in the same cell would provide more definitive proof of this apparent correlation. Thus, following exposure to vehicle or the calcium chelator BAPTA (1-20 μM), primary cortical neurons were labeled with Calcium Green-1 which was then cross-linked with EDAC, prior to immunostaining for various proteins. We found that BAPTA-induced changes in calcium were highly correlated with changes in expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…Perhaps at low BAPTA concentrations chelation-induced changes in calcium fall within a physiological range, mimicking natural buffering of this ion by CaBPs, and so recovery was possible. At higher BAPTA concentrations, calcium chelation is more robust, taking calcium levels well outside any physiological range, and pathological effects become apparent (indeed, we have previously noted abrupt increases in cell death when transitioning from low to high BAPTA concentrations (Turner et al 2007a)). …”
Section: Network Establishmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Perhaps at low BAPTA concentrations chelation-induced changes in calcium fall within a physiological range, mimicking natural buffering of this ion by CaBPs, and so recovery was possible. At higher BAPTA concentrations, calcium chelation is more robust, taking calcium levels well outside any physiological range, and pathological effects become apparent (indeed, we have previously noted abrupt increases in cell death when transitioning from low to high BAPTA concentrations (Turner et al 2007a)). …”
Section: Network Establishmentmentioning
confidence: 84%
“…However, even within the same study, both low and high neuronal calcium levels have been shown to induce growth cone collapse (Mattson and Kater 1987;Kater et al 1988), suggesting that growth cone motility, as well as neurite growth and arborization, may require optimal levels of calcium, deviations above or below which result in negative outcomes. Similarly, neuronal survival may depend on maintaining a "calcium set point," first proposed by Eugene Johnson (Johnson et al 1992) and later used by our group to explain neuronal death observed in P7 rats exposed to MK801 (Turner et al 2002;Turner et al 2007a;Turner et al 2007b). Indeed, more recently we have shown that MK801-induced injury in P7 rats is observed in cells that lack the CaBPs calbindin-D28K, calretinin, or parvalbumin (Lema Tomé et al 2006).…”
Section: Calcium and Neuronal Maturationmentioning
confidence: 91%
“…2 The observation that not only high Ca 2+ overload 3 but also Ca 2+ antagonists, 4 reducing [Ca 2+ ] c , can cause neuronal death, has raised the hypothesis that Ca 2+ ions behave as both cell survival supporters and cell death promoters, depending on both amplitude and temporal extension of the cell Ca 2+ signal, together with other physiological conditions. 5 Hence, there has to be a critical set point where Ca 2+ -derived cytoprotective signals might turn into cytotoxic. 6 In this framework, the relationship between Ca 2+ dysregulation and neuronal death has been well-documented in several neurodegenerative diseases, such as Parkinson's disease, 7 cerebral ischemia, 8 and amyotrophic lateral sclerosis.…”
Section: + Concentrations ([Camentioning
confidence: 99%
“…Ketamine is a non-competitive N-methyl-D-aspartate (NMDA) antagonist that disrupts calcium homeostasis in neurons (Sinner et al, 2005;Slikker et al, 2007). Since calcium signaling has an important role in cytoskeleton stability (Lankford and Letourneau, 1989) as well as neuronal viability (Turner et al, 2007;Ringler et al, 2008), ketamineinduced calcium deregulation may lead to alterations in axonal outgrowth and induction of apoptotic cell death (Wang et al, 2005;Turner et al, 2012;Bai et al, 2013;Dong and Anand, 2013).…”
Section: Introductionmentioning
confidence: 99%